2016
DOI: 10.1111/ijcp.12784
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen testing rates and referral patterns from general practice data in England

Abstract: Background: There is currently no national screening programme for prostate cancer in England, but eligible men can request a prostate-specific antigen (PSA) test from their general practitioner (GP). There are no routinely available data to monitor the extent of PSA testing and referral. Aim: The aim of this study was to investigate the rate of PSA testing in general practice and subsequent patterns of referral. person-years were tested at least once in 2010, and 9.45 (95% CI 9.37-9.53) in 2011. Rates increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 15 publications
3
18
1
Order By: Relevance
“…However prior to this, in 2007, a small survey was undertaken on GP knowledge of PSA testing in asymptomatic men and the similarities to the PCRMP guidance, with 21 GPs from 18 GP practices in Oxfordshire; which showed that more GP education was needed on PSA testing (15). In addition the Clinical Practice Research Datalink (CPRD) PSA testing rates and referral patterns study that was carried out with this study, showed that PSA testing rates increased from 2010 to 2011, GPs often retest patients with raised PSA levels before referral and overall referral is low, which further supports the findings of this study and the need for increased guideline awareness and GP education (16).…”
Section: Comparison With Existing Literaturesupporting
confidence: 77%
“…However prior to this, in 2007, a small survey was undertaken on GP knowledge of PSA testing in asymptomatic men and the similarities to the PCRMP guidance, with 21 GPs from 18 GP practices in Oxfordshire; which showed that more GP education was needed on PSA testing (15). In addition the Clinical Practice Research Datalink (CPRD) PSA testing rates and referral patterns study that was carried out with this study, showed that PSA testing rates increased from 2010 to 2011, GPs often retest patients with raised PSA levels before referral and overall referral is low, which further supports the findings of this study and the need for increased guideline awareness and GP education (16).…”
Section: Comparison With Existing Literaturesupporting
confidence: 77%
“…The proportion of patients who underwent a PSA screening in our study performed in France is much higher than those reported by other authors [23][24][25][26][27][28][29][30]. For men aged 50-74 years, the observed 41.05% rate of French patients who had undergone a PSA screening is comparable to the participation in systematic screenings for colorectal cancer or breast cancer.…”
Section: Discussioncontrasting
confidence: 66%
“…A more recent study analysed data from patient electronic records in primary care for men aged 45–84 years. It reported that for every 100 men enrolled with a general practitioner (GP) for one year, 5.03 (asymptomatic men) were tested in 2010, and the rate increased by 8% in 2011 to 5.45 per 100 5. Note that the data this analysis was based on represent only 5% of the population in England and may not be representative of all practices.…”
Section: Introductionmentioning
confidence: 99%